(untitled) (Revista Direito em Debate, 2022)
The research aims to verify whether the Labor Reform and Provisional Labor Measures of Covid-19 have shaken the autonomy of Labor Law, by affecting the principles of Labor Law. To this end, it seeks to answer: how did the changes promoted by the Labor Reform Law, the Provisional Labor Measures in the pandemic affect the prevalence of the principles / reasons of Labor Law and its own teleology? The research method was mixed because it used the hypothetical-deductive method, in addition to bringing qualitative results. A questionnaire was applied to the research participants, duly authorized by the Ethics Committee of the Brazil platform with CAAE number 22472919.1.0000.0018, from January 20 to 24, 2020. The path taken considered: the reflection on the principles of Labor Law; Provisional Measures nº 927 and 936/2020; and the results. The result of the research demonstrates that Labor Law continues to be an autonomous branch that has suffered shakes in its principles, including the inclusion of the principle of minimum intervention in collective autonomy and the adoption of interpretation, as well as it was observed that the application of Labor Law will consider the conformity with Constitutional Law and International Labor Law Conventions.